The Structure of compact groups : a primer for the student, a handbook for the expert - Hofmann, Karl Heinrich; Morris, Sidney A., 1947- (De Gruyter studies in mathematics, 2013)
Dealing with subject matter of compact groups that is frequently cited in fields like algebra, topology, functional analysis, and theoretical physics, this book - now in its third revised and augmented edition - has been conceived with the dual purpose of providing a text book for upper level graduate courses or seminars, and of serving as a source book for research specialists who need to apply the structure and representation theory of compact groups. After a gentle introduction to compact groups and their representation theory, the book presents self-contained courses on linear Lie groups.